Konsep Ketubuhan dalam Asmara Berdarah Ken Arok Ken Dedes: Kajian Feminisme Simone De Beauvoir - Jalu Norva Illa Putra (Udayana University, 2021)
The discussion about feminism never ceases to be debated in all aspects. Women and men are always contested about who is